METODE PEMBUKTIAN OTOPSI BARU DALAM KASUS TINDAK PIDANA PEMBUNUHAN - Descaperine, Melati; Zarzani, T Riza; Anwar, Yohny; Sinaga, Hary Angga; Fauzan, Fauzan (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The problem of verbal autopsy as one of the evidence in cases of murder and legal consequences if the results of the verbal autopsy are different from other legal evidence in court. Research using the statutory approach and the case approach, the following conclusions are obtained: Verbal autopsy as referred to in Article 184 of the Criminal Procedure Code, verbal autopsy in the form of letters containing the results of interviews with doctors or midwives or nurses who have expertise, related to the death of people outside the service health according to the Cooperation Regulation Number 162 / Menkes / PB / I / 2010 concerning Reporting of Deaths and Causes of Death, that every death that occurs outside the health service facility must be traced to the cause of death. Verbal autopsy in the form of a letter from the results of interviews by trained interviewers, so that it is only a description of the cause of death of someone outside the health service. The legal consequence is if the information as a result of the verbal autopsy is different from other legal evidence in the trial, considering that the verbal autopsy is a letter including as an indication, if the instructions are compatible with one another, as well as with the criminal act itself, it indicates that the a criminal act occurred and who was the perpetrator as stated in Article 188 of the Criminal Procedure Code.